Factors affecting the severity of European winter windstorms - Moran, Thomas (2021)
Every year, dozens of intense extra-tropical cyclones strike Europe with high intensity windfields — or windstorms — that inflict significant damage to local infrastructure and housing. In terms of reinsurance losses, windstorms are the most socioeconomically dangerous hazards affecting Europe to date. Stakeholders from both the public and private sectors are interested in improving the predictability of these systems, and while substantial advancements have been made towards a better understanding of their occurrence frequency, little has been explored in terms of their potential severity. Thus, the thesis focuses on the factors affecting the severity (or footprint) of European windstorms by taking a large set of events from the MPI-ESM-LR model, and ERA-20C reanalysis data. After defining a windstorm footprint metric, windstorms are objectively matched to unique cyclones, where it is assumed the windstorm is created by its paired cyclone (the paired system is called a “storm”). These storms form the basis of the systems studied in the thesis as they provide more upstream information. Factors are explored in three core topics: i) characterising European windstorms in terms of their parent cyclones; ii) exploring the role of various cyclonic growth factors (CGFs) on storm footprints; and iii) using a Generalized Linear Model (GLM) to quantitatively rank the importance of factors affecting these footprints. In terms of their parent cyclones, it is found that extremely high windstorm footprints are associated with deeper and faster-growing cyclones, and non-extreme systems show a weaker relationship. Strong windstorms are additionally associated with bomb cyclones. Windstorms usually form 2 days after cyclogenesis and are found to intensify in a 24-hour window centered on cyclone maximum intensification. Finally, we investigated the cyclone pathways which create high European windstorm footprints. Cyclogenesis maxima are situated over the North Atlantic, with a higher density towards the West near the US East ...